2015
DOI: 10.1038/ki.2015.194
|View full text |Cite
|
Sign up to set email alerts
|

Increased circulating sclerostin levels in end-stage renal disease predict biopsy-verified vascular medial calcification and coronary artery calcification

Abstract: Sclerostin, an osteocyte-derived inhibitor of bone formation, is linked to mineral bone disorder. In order to validate its potential as a predictor of vascular calcification, we explored associations of circulating sclerostin with measures of calcification in 89 epigastric artery biopsies from patients with end-stage renal disease. Significantly higher sclerostin levels were found in the serum of patients with epigastric and coronary artery calcification (calcification score 100 or more). In Spearman's rank co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
113
2
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 118 publications
(121 citation statements)
references
References 43 publications
4
113
2
2
Order By: Relevance
“…A second possible explanation for the positive association between sclerostin levels and increased prevalence and severity of vascular calcification may be that the former is lowered as a compensatory mechanism to counterbalance calcification caused by other mechanisms. This may be paradoxically supported by clinical studies that showed a positive association between sclerostin levels and vascular calcification [31,32]. In our study, we observed a U-shaped association between serum sclerostin levels and aortic AoAC, suggesting that 2 nd tertiles of serum sclerostin levels (161 -260 pg/mL) may be associated with the inhibition of vascular calcification.…”
Section: Discussioncontrasting
confidence: 62%
“…A second possible explanation for the positive association between sclerostin levels and increased prevalence and severity of vascular calcification may be that the former is lowered as a compensatory mechanism to counterbalance calcification caused by other mechanisms. This may be paradoxically supported by clinical studies that showed a positive association between sclerostin levels and vascular calcification [31,32]. In our study, we observed a U-shaped association between serum sclerostin levels and aortic AoAC, suggesting that 2 nd tertiles of serum sclerostin levels (161 -260 pg/mL) may be associated with the inhibition of vascular calcification.…”
Section: Discussioncontrasting
confidence: 62%
“…It should also be pointed out that VC might vary depending on arterial type and location along any specific artery. However, we reported a close relation between epigastric artery medial calcification and extent of coronary artery calcification [44]. Finally, since RNA was prepared from a homogenised arterial sample, this precludes any knowledge on how the expression varied between different cell types.…”
Section: Discussionmentioning
confidence: 99%
“…It is tempting to hypothesize that this might be caused by greater sclerostin expression and thus explain our findings. On the other hand in the paper by Quershi et al [27], the authors conclude, that plasma sclerostin levels predict the magnitude of vascular calcification, still it is yet unknown if the increased concentrations of sclerostin are the cause, or effect of the increased calcification of the vasculature.…”
Section: Discussionmentioning
confidence: 99%